Immunogenicity Risk Assessment of Spontaneously Occurring Therapeutic Monoclonal Antibody Aggregates - Swanson, Michael D.; Rios, Shantel; Mittal, Sarita; Soder, George; Jawa, Vibha (Frontiers in Immunology, 2022)
Aggregates of therapeutic proteins have been associated with increased immunogenicity in pre-clinical models as well as in human patients. Recent studies to understand aggregates and their immunogenicity risks use artificial stress methods to induce high levels of aggregation. These methods may be less biologically relevant in terms of their quantity than those that occur spontaneously during processing and storage. He we describe the immunogenicity risk due to spontaneously occurring therapeutic antibody aggregates using peripheral blood mononuclear cells (PBMC) and a cell line with a reporter gene for immune activation: THP-1 BLUE NFkB. The spontaneously occurring therapeutic protein aggregates were obtained from process intermediates and final formulated drug substance from stability retains. Spontaneously occurring aggregates caused innate immune responses for several donors in a PBMC assay with cytokine and chemokine production as a readout for immune activation. Meanwhile, no significant adaptive phase responses to spontaneously occurring aggregate samples were detected. While the THP-1 BLUE NFkB cell line and PBMCs assays both responded to high stress induced aggregates, only the PBMCs from a limited subset of donors responded to processing-induced aggregates. In this case, levels of antibody aggregation occurring at process relevant levels are lower than those induced by stirring and may pose lower risk in vivo. Our methodologies can further inform additional immunogenicity risk assessments in a pre-clinical model.